Analisis Kebijakan Pemerintah dalam Mendukung Perkembangan Industri Halal: A Sytematic Literature Review - Bastian, Rifqya Azzahra; Fitri, Cut Dian (Yayasan Putroe Ceudah Aceh, 2025)
The halal industry is experiencing rapid growth along with the increasing demand for halal products in domestic and international markets. The government plays a strategic role in creating a conducive ecosystem through supportive regulations and policies, such as halal certification standards, incentives for business actors, and product quality control. However, the effectiveness of these regulations and policies in encouraging the development of the halal industry still requires in-depth analysis. This study uses a systematic literature review method with the PRISMA model to examine the latest literature related to government regulations and policies in the development of the halal industry. The literature search was conducted in the Google Scholar database with a period of 2020–2025 and relevant keywords. The review results indicate that clear and integrated halal certification standards increase consumer trust and expand market access, while incentive policies and strengthening certification bodies encourage innovation and business growth. However, implementation challenges such as lack of coordination between institutions and differences in certification standards between countries still hamper the optimal development of the halal industry. This study identifies conceptual and practical gaps in the literature that need to be addressed to strengthen the halal industry ecosystem sustainably. These findings provide an important contribution to the development of more effective policies to support the growth of the halal industry and enhance the competitiveness of halal products in the global market.